The role of hearing professionals for over-the-counter hearing aids - Perez-Heydrich, Carlos A.; Zenczak, Colleen; Roque, Lindsey; Ryan, Colleen; Agrawal, Yuri; Sayyid, Zahra N. (Frontiers in Audiology and Otology, 2023)
Adults with all levels of hearing loss have faced financial and accessibility constraints in obtaining prescription hearing aids. To increase access to hearing aids, the Food and Drug Administration (FDA) has created a new designation of over-the-counter (OTC) hearing aids for adults with perceived mild to moderate hearing loss. The goal of this article is to describe the incorporation of OTC hearing aid users into established audiology services. A proposed workflow was created by otolaryngologists and audiologists at Johns Hopkins University School of Medicine and is being implemented at outpatient audiology offices. We used published criteria for appropriate OTC hearing aid usage and disqualifying criteria hearing specialists should be aware of. The proposed workflow describes the multiple entry points for OTC hearing aid users seeking access to care and appropriate objectives for these visits. The new FDA ruling has increased the accessibility of hearing assistance devices; however, the varying degrees of retailer support systems could lead to improper fitting and other technical problems for some patients trialing new hearing aids. Our proposed workflow aims to describe the incorporation of established hearing assistance services with the new OTC hearing aid market.